Skipped spawning in a protandric hermaphrodite: Elucidating the physiological mechanisms in common snook Centropomus undecimalis using reproductive biology and energetics - Alexis A. Trotter; Jared L. Ritch; Jessica L. Carroll; Kristin L. Cook; Gregory V. Onorato; Kristen W. Rynerson; David O. Westmark; Colin P. Shea (Journal of Fish Biology, 2026)
Recent acoustic telemetry research has demonstrated that a portion of the common snook Centropomus undecimalis population in Florida skips annual spawning; however, the details of why some individuals skip spawning are unclear. We conducted a comprehensive study of C. undecimalis reproductive biology to determine if a certain population demographic (e.g. size, age, sex, biological condition) skips spawning in a representative estuary in Florida (Tampa Bay). Reproductive parameters, specifically histological examination of ovaries and testes, analysis of reproductive hormone levels and estimates of energetics including fish condition, hepatosomatic and mesenteric fat indices, were analysed for 254 females and 210 males over two consecutive spawning seasons (2016 and 2017). The results agreed with the known reproductive biology of the species and provided a more comprehensive description of developmental patterns throughout the spawning season. Fish that skipped spawning, defined here as an individual of reproductively mature size having both undeveloped gonads and undetectable levels of primary hormone (17β‐estradiol in females, 11‐ketotestosterone in males), represented 18% of fish sampled. Skip spawning individuals were collected from both estuarine and riverine sites, and were predominately smaller and younger females that had spawned at least once previously as females. Fish that skipped spawning had a lower body condition, a lower fat index and, in particular, a lower liver index. As skipped spawning was predominately observed in younger and smaller female C. undecimalis that were energetically depleted, we suggest that the combination of sex transition from male to female, followed by participation in spawning in the next season, leads to most instances of skipped spawning for the species.